Manifestation of the Anti-Corruption Education Movement in Breaking the Growth of New Regeneration of Corruptors - Anggriawan, Kevlin; Ahmad, Endang; Nurgiansah, T Heru (CV. Rayyan Dwi Bharata, 2024)
Corruption is a disease that is difficult to eliminate on this earth, not least in Indonesia where the Corruption Perception Index is very high. To deal with this is not an easy matter, we need preventive and curative efforts, namely by providing education to the younger generation today, namely Anti-corruption Education. Anti-corruption education is not a powerful way to eliminate all acts of corruption, but the existence of these educational activities will intuitively awaken the human conscience to realize not to commit criminal activities such as corruption. This article will reveal an action method on how to conduct real anti-corruption education for the younger generation to make them realize how dangerous corruption is for the people around them. This article uses a literature study method consisting of searching for articles from various theoretically supporting sources through SAGE Journals, Google Scholar, and supporting books to perfect the results of writing this article. The results of this research will comprehensively describe the real Anti-Corruption Education to be taught to the younger generation not only in theory, but together with real action actions such as campaigns to persuasively invite people to get involved in efforts to prevent corrupt practices. The younger generation is at the forefront of guarding the future of the country, therefore the younger generation should not be hypnotized by the temptation of corruption, because if they are tempted, it can destroy this country in an instant.